2007
DOI: 10.3138/1457-2411-v402-62l1
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Gait Analysis to Contribute to Differential Diagnosis of Early Stage Dementia: Current Research and Future Directions

Abstract: Early differential diagnosis of dementia is becoming increasingly important as new pharmacologic therapies are developed, as these treatments are not equally effective for all types of dementia. Early detection and differential diagnosis also facilitates informed family decision making and timely access to appropriate services. Information about gait characteristics is informative in the diagnostic process and may have important implications for discriminating among dementia subtypes. The aim of this review pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 69 publications
0
28
0
1
Order By: Relevance
“…Walking is a task that requires cognitive input, particularly in the domains of attention and executive functioning [6][7][8][9]. Balance, the ability to maintain postural control, also requires cognitive input [10]. Hence, changes in cognitive function contribute to gait disturbances, balance disorders, and increased fall risk [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…Walking is a task that requires cognitive input, particularly in the domains of attention and executive functioning [6][7][8][9]. Balance, the ability to maintain postural control, also requires cognitive input [10]. Hence, changes in cognitive function contribute to gait disturbances, balance disorders, and increased fall risk [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have identified gait as an important marker in early identification of vascular dementia [8], [9], [16], [38], while some other researchers have identified executive function as an early marker for subcortical vascular dementia [33], [35]- [37]. We are proposing a framework that combines gait and executive function as a hybrid early predictor of subcortical vascular dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring changes in gait pattern or alterations in the center of mass enables tracking the changes in gait after a significant cardiovascular event. Gait analysis can be traced back to the early eighties where the analysis was done to in the assessment of cerebral palsy, neuromuscular disorders and other orthopedic evaluations [33].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations